Impact of Fixed Asset Revaluation Practice on Investor Perception in Bangladesh Stock Market - Rahman, Md. Tahidur; Hossain, Syed Zabid (International Journal of Economics, Management and Accounting, 2022)
This study intends to demonstrate empirical evidence concerning investor perception of fixed asset revaluation (FAR) practices by publicly traded companies in Bangladesh. The sample used in this study consisted of 191 general and institutional investors selected based on the convenience sampling technique. A structured questionnaire containing a five-point Likert scale was used to gather information concerning investor perceptions. A majority (87%) of the respondents believe that the fairly-practiced FAR model is better than the cost model to show the real picture of companies’ fixed assets. Respondents reveal their doubts about the motives and fairness of the FAR model in Bangladesh. Around 86% of the respondents agreed that companies resort to FAR mainly to increase their stock prices. Some 90% of the respondents agreed that companies practiced FAR to achieve easy access to loans. A significant number of investors believe that FAR had an active role in creating the stock market bubbles and their subsequent bursts in Bangladesh. The current study’s findings provide valuable pointers to investors, regulators, and other stakeholders. Since investors view FAR with suspicion, regulators should enforce relevant statutes to avoid motivated, manipulated, and selective disclosure.